Why Green Hotels Have Not Become The Main Choice For Indonesian Consumers: An Academic Analysis - Putri, Lily (Journal Business Administration: Entrepreneurship and Creative Industry, 2025)
The concept of Green Hotel is part of a sustainable business strategy that integrates environmentally friendly practices within the global hospitality industry. Although global trends indicate a significant increase in consumer preference for eco-friendly accommodations, this phenomenon not been equally adopted in Indonesia. This study aims to analyze the factors causing the gap between green hotel campaigns and the responses of Indonesian consumers. Using a qualitative approach based on literature review and secondary data, the research found a discrepancy between consumers' positive attitudes and their actual behaviors, influenced by factors such as price, low environmental education, a consumption culture that is not yet environmentally supportive, and inconsistent implementation by hotels. The study recommends a collaborative strategy involving the hotel industry, government, and consumers to enhance understanding, trust, and value toward green hotel practices in Indonesia.